Bundling Product Program as A Marketing Public Relations Strategy of Erafone Mal-Pik-Avenue in Maintaining Brand Awareness - Rizka Septiana; Michelle Laavinia (ULTIMA Comm, 2025)
This research is motivated by the emergence of negative reviews on the Google Review platform, which have the potential to threaten the company’s positive image and Erafone’s position as a leading smartphone retail company. As part of PT Erajaya Swasembada Tbk, a company engaged in the distribution and sales of information and communication technology products.The purpose of this study is to explain how the bundling program is designed within the framework of the MPR communication strategy, in line with the Three Ways Strategies concept, to share public opinion, strengthen brand image, and enhance brand awareness. This study employs a descriptive qualitative approach by analyzing Erafone Mal PIK Avenue’s communication strategy in implementing the product bundling program as part of its MPR activities. The results show that MPR activities such as News, Publication, Speech, Public Service Activities, Identity Media, Event, and Sponsorship are considered effective in supporting the company’s various products to achieve competitive advantage and build a consistent brand image.. Overall, Erafone’s communication strategy focuses not only on promotion but also on strengthening public relations and creating a sustainable customer experience.